Hydrogen Sulfide Is a Novel Protector of the Retinal Glycocalyx and Endothelial Permeability Barrier - Allen, Claire L.; Wolanska, Katarzyna; Malhi, Naseeb K.; Benest, Andrew V.; Wood, Mark E.; Amoaku, Winfried; Torregrossa, Roberta; Whiteman, Matthew; Bates, David O.; Whatmore, Jacqueline L. (Frontiers in Cell and Developmental Biology, 2021)
Significantly reduced levels of the anti-inflammatory gaseous transmitter hydrogen sulfide (H2S) are observed in diabetic patients and correlate with microvascular dysfunction. H2S may protect the microvasculature by preventing loss of the endothelial glycocalyx. We tested the hypothesis that H2S could prevent or treat retinal microvascular endothelial dysfunction in diabetes. Bovine retinal endothelial cells (BRECs) were exposed to normal (NG, 5.5 mmol/L) or high glucose (HG, 25 mmol/L) ± the slow-release H2S donor NaGYY4137 in vitro. Glycocalyx coverage (stained with WGA-FITC) and calcein-labeled monocyte adherence were measured. In vivo, fundus fluorescein angiography (FFA) was performed in normal and streptozotocin-induced (STZ) diabetic rats. Animals received intraocular injection of NaGYY4137 (1 μM) or the mitochondrial-targeted H2S donor AP39 (100 nM) simultaneously with STZ (prevention) or on day 6 after STZ (treatment), and the ratio of interstitial to vascular fluorescence was used to estimate apparent permeability. NaGYY4137 prevented HG-induced loss of BREC glycocalyx, increased monocyte binding to BRECs (p ≤ 0.001), and increased overall glycocalyx coverage (p ≤ 0.001). In rats, the STZ-induced increase in apparent retinal vascular permeability (p ≤ 0.01) was significantly prevented by pre-treatment with NaGYY4137 and AP39 (p < 0.05) and stabilized by their post-STZ administration. NaGYY4137 also reduced the number of acellular capillaries (collagen IV + /IB4-) in the diabetic retina in both groups (p ≤ 0.05). We conclude that NaGYY4137 and AP39 protected the retinal glycocalyx and endothelial permeability barrier from diabetes-associated loss of integrity and reduced the progression of diabetic retinopathy (DR). Hydrogen sulfide donors that target the glycocalyx may therefore be a therapeutic candidate for DR.